Mapping digital competences of modern languages students (2015)
During recent years, digital competence has become a key concept in the discussion of which skills and understanding people should have in the knowledge society. This article presents the results of a research project that set out to describe digital natives’ perceptions of their ICT competences. A mixed case study approach was used, applying a survey to collect data based on three proposed dimensions: instrumental, socio-communicative, and axiological. Among the main findings, it was possible to describe the way digital natives interact with ICT tools, and the tendencies in their use for social and communicative purposes.